Medical students' perceptions of video-linked lectures and video-streaming - Karen Mattick; RuoLan Wang; Elisabeth Dunne (Association for Learning Technology, 2010)
Video-linked lectures allow healthcare students across multiple sites, and between university and hospital bases, to come together for the purposes of shared teaching. Recording and streaming video-linked lectures allows students to view them at a later date and provides an additional resource to support student learning. As part of a UK Higher Education Academy-funded Pathfinder project, this study explored medical students' perceptions of video-linked lectures and video-streaming, and their impact on learning. The methodology involved semi-structured interviews with 20 undergraduate medical students across four sites and five year groups. Several key themes emerged from the analysis. Students generally preferred live lectures at the home site and saw interaction between sites as a major challenge. Students reported that their attendance at live lectures was not affected by the availability of streamed lectures and tended to be influenced more by the topic and speaker than the technical arrangements. These findings will inform other educators interested in employing similar video technologies in their teaching.Keywords: video-linked lecture; video-streaming; student perceptions; decisionmaking; cross-campus teaching.